HUBUNGAN JARAK TEMPAT TINGGAL DAN PENGETAHUAN MASYARAKAT DENGAN PEMANFAATAN PELAYANAN KESEHATAN - Sasmita S, Muhammad Andika; Roziah, Roziah (JURNAL KESEHATAN TERAPAN, 2021)
Good health center health services do not necessarily guarantee the number of patients visiting. This must also be supported by the accuracy and capacity of the puskesmas in serving community needs such as communication, time, quality and quantity of products and services, excellent service. This type of research is analytic survey with cross sectional study approach. With the sample of this study were all patients who went to the Puskesmas, amounting to 89 people. The results of this study indicate that of the 89 respondents studied, 45 respondents (50.6%) utilized health services, 45 respondents (50.6%) utilized health services. Suggestion: provide information about the importance of using the Puskesmas as the right place for treatment. Key words : Utilization of Health Services